Bicaudal-C Post-transcriptional regulator of cell fates and functions - Dowdle, Megan E.; Kanzler, Charlotte R.; Harder, Cole R. K.; Moffet, Samuel; Walker, Maya N.; Sheets, Michael D. (Frontiers in Cell and Developmental Biology, 2022)
Bicaudal-C (Bicc1) is an evolutionarily conserved RNA binding protein that functions in a regulatory capacity in a variety of contexts. It was originally identified as a genetic locus in Drosophila that when disrupted resulted in radical changes in early development. In the most extreme phenotypes embryos carrying mutations developed with mirror image duplications of posterior structures and it was this striking phenotype that was responsible for the name Bicaudal. These seminal studies established Bicc1 as an important regulator of Drosophila development. What was not anticipated from the early work, but was revealed subsequently in many different organisms was the broad fundamental impact that Bicc1 proteins have on developmental biology; from regulating cell fates in vertebrate embryos to defects associated with several human disease states. In the following review we present a perspective of Bicc1, focusing primarily on the molecular aspects of its RNA metabolism functions in vertebrate embryos.